Factors That Influence Teenage Smoking Behavior In SMAN 1 Geger Madiun District - Purnamasari, Vivien Dwi; Ambarwati, Lucka Febrian; Kirana, Gerardin Ranind; Nugraheni, Reny (Universitas Pekalongan, 2024)
Smoking is a risky behavior for teenagers.Factors that affect teenage smoking behavior include psychosocial factors, parental permissiveness, and peer influence. The purpose of the study to describe the factors that affect teenager smoking behavior at the Senior High School of Geger Madiun District. Psychosocial factor variables will measure smoking habits, cigarette addiction, the benefits of smoking that can make you feel happy and relaxed, and the benefits of smoking that can lower emotions. The variable of parental permissive attitude will be seen from parents giving them the freedom to smoke and the variable of association with peers will be measured by the intensity of association with friends and how much influence peers have. The sample in the study was 100 respondents with a simple random sampling technique with the research criteria, namely respondents who are not illiterate. The type research used descriptive quantitative with cross sectional design. The result of this study using the Normality test value (p=0,065) more than a significance value of 0,05 which indicate that the data is normally distributed, so the data ≥ mean, 52 people (53%) are affected by smoking behavior from psychosocial factors, 56 people ( 52%) had permissive parents who smoked, 64 people (64%) were influenced by their peers smoking behavior. It is recommended that the school conduct extra supervision, contribute penalty smoking prohibition, conduct sudden raid, and conduct socialization to parents about the dangers of smoking.